Preface: GROWTH OF BUSINESS AND SOCIETY IN POST CRISIS PERIOD - Kume, Vasilika (European Scientific Journal, ESJ, 2021)
Coronavirus is pushing economies towards economic recession, at a time when all parameters and trends were positive. Social distancing is turning into economic distancing. Leading economists are proposing â€œextreme reformsâ€ to fight the economic catastrophe that could be caused by the COVID-19 pandemic. There is a consensus among analysts and experts in various fields that after the end of the COVID-19 pandemic, â€œnothing will be the sameâ€. It will be a â€œnew realityâ€, with many changes in lifestyle and way of doing business. However, one of the expectations is changes in customer behavior.